PENGARUH STRATEGIGENERATIVE LEARNING TERHADAP PEMAHAMAN KONSEP MATEMATIS SISWA KELAS VII SMP NEGERI 2 BATANG KAPAS TAHUN PELAJARAN 2013/2014 - Sumarni, Titin; Aima, Zulfitri; Yuliana Fitri, Dewi (STKIP PGRI Sumbar, 2014)
ABSTRACTÂ This purpose of the research a students activities progress and Â was to study whether the mathematic conceptual understanding of the students taught by using generative learningÂ strategy was better than that of students taught by using conventional learning in class VII of SMP Negeri 2 Batang Kapas. This was an experimental.The population of the research was the student in class VII registered in academic year 2013/2014. The instrument of the research was observation sheet and a posttest whose reliability was 0,75. The data collected was analyzed by using t-test. Based on the result of data analysist, it was found that the average score of the students in the experimental class (78,58) was higher than those in the control class (66,63).Tthe result of statistical test indicated that the value of tcalculated (7,986) was bigger than ttable (1,645). Based on these results, it was concluded that the mathematic conceptual understanding of the students taught by using generative learning strategy was better than that of students taught by using conventional learning in class VII of SMP Negeri 2 Batang Kapas.